STRATEGI PENGEMBANGAN GUA RANGKO SEBAGAI DAYA TARIK WISATA ALAM BERBASIS MASYAKARAKAT DI KECAMATAN BOLENG KABUPATEN MANGGARAI BARAT-NUSA TENGGARA TIMUR - I Nyoman Parta; Nur Arafah (Forum Manajemen STIMI Handayani Denpasar, 2020)
The purpose of this research is to find out the potential of Rangko Cave Tourism and to know the obstacles in the development process. The type of data used in this study is qualitative data and quantitative data, with data sources namely primary data and secondary data. Data collection techniques were carried out by means of observation, interviews, and documentation studies, while data analysis techniques used were the analysis of strength, weakness, oopportunities, threats (SWOT) and the SWOT matrix. The results of this study indicate that there is a lot of potential that has the attraction of Rangko Cave Tourism that can be developed. But unfortunately there are still many shortcomings contained in the development process ranging from low Human Resources to inadequate facilities. To overcome these obstacles needed a development strategy that is suitable for the Rangko Cave Tourism Attraction and with these strategies it is expected that the development of the Rangko Cave Tourism Attraction will run even better in the future.